Examining factors that could lead to unethical behaviour in institutions of higher learning - Nurul Khair, Ishak; Hasnah, Haron; Ishak, Ismail (UMP Press, 2019)
Issues related to unethical behaviour is also evident in institutions of higher learning. This paper will discuss some of the factors that have been shown to have an influence on unethical behaviour in the specific context in higher learning institutions in Malaysia. Ethical leadership and ethical climate are identified to be the variables that might influence the intention to perform such behaviour. It then discusses the importance of ethical leadership and ethical climate in shaping the ethical conduct in higher learning institutions.